EFFECTS OF ENERGY ON POLLUTION: AN OVERVIEW - Dr. Pijush Kanti Tripathi, (The Bioscan, 2024)
Nuclear energy has become an essential part of the low-carbon energy mix as countries work to battle climate change and cut carbon emissions. Even though fossil fuels are still the world's most popular energy source, reducing pollution and combating climate change require a shift to greener energy sources like nuclear power and renewable energy. In this paper, an overview of the effects of various energy sources on pollution is given in this review, which also looks at how they affect the quality of the air, water, and soil in addition to climate change.